-3 / 8 + 12/ 25 - 5/8 + 2/-5 + 13/25
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.


-3/8+12/25+5/-8+2/-5+13/25
=(3/8+5/-8)+12/25+2/-5+13/25
=-1+12/25+2/-5+13/25
=-13/25+2/-5+13/25
=-23/25+13/25
=-2/5

\(\dfrac{-3}{8}+\dfrac{12}{25}+\dfrac{5}{-8}+\dfrac{2}{-5}+\dfrac{13}{25}\)
\(=\dfrac{-3}{8}+\dfrac{12}{25}+\dfrac{-5}{8}+\dfrac{-2}{5}+\dfrac{12}{25}\)
\(=\left(\dfrac{-3}{8}+\dfrac{-5}{8}\right)+\left(\dfrac{12}{25}+\dfrac{12}{25}+-\dfrac{2}{5}\right)\)
Còn lại bn tự tính nhé!
\(\dfrac{-3}{8}\) + \(\dfrac{12}{25}\) + \(\dfrac{5}{-8}\) + \(\dfrac{2}{-5}+\dfrac{13}{25}\)
= \(\left(\dfrac{-3}{8}+\dfrac{5}{-8}\right)+\left(\dfrac{12}{25}+\dfrac{13}{25}\right)+\dfrac{2}{-5}\)
= \(\left(\dfrac{-3}{8}+\dfrac{-5}{8}\right)+1+\dfrac{-2}{5}\)
= 1 + 1 + \(\dfrac{-2}{5}\)
= \(\dfrac{8}{5}\)

A=2/7+-3/8+11/7+1/3+1/7+5/-8
A=(2/7 + 1/7 + 11/7) + (-3/8 + 5/-8) + 1/3
A=2 + (-1) + 1/3
A=1 + 1/3
A=4/3
B=-3/8+12/25+5/-8+2/-5+13/25
B=(-3/8 + 5/-8) + (12/25 + 13/25) + 2/-5
B=-1 + 1 + 2/-5
B=-2/5

\(A=\left(\dfrac{2}{7}+\dfrac{11}{7}+\dfrac{1}{7}\right)+\left(\dfrac{-3}{8}+\dfrac{-5}{8}\right)+\dfrac{1}{3}=2-1+\dfrac{1}{3}=1+\dfrac{1}{3}=\dfrac{4}{3}\)
\(B=\dfrac{-3}{8}+\dfrac{12}{25}+\dfrac{-5}{8}+\dfrac{-2}{5}+\dfrac{13}{25}=1+1-\dfrac{5}{8}=-\dfrac{5}{8}\)

\(A=\frac{2}{7}+\left(-\frac{3}{8}\right)+\frac{11}{7}+\frac{1}{3}+\frac{1}{7}+\left(-\frac{5}{8}\right)\)
\(=\left(\frac{2}{7}+\frac{11}{7}+\frac{1}{7}\right)+\left(-\frac{3}{8}-\frac{5}{8}\right)+\frac{1}{3}\)
\(=2-1+\frac{1}{3}\)
\(=1+\frac{1}{3}\)
\(=\frac{4}{3}\)
\(B=-\frac{3}{17}+\left(\frac{2}{3}+\frac{3}{17}\right)\)
\(=-\frac{3}{17}+\frac{2}{3}+\frac{3}{17}\)
\(=\left(-\frac{3}{17}+\frac{3}{17}\right)+\frac{2}{3}\)
\(=0+\frac{2}{3}\)
\(=\frac{2}{3}\)
\(C=\frac{3}{8}+\frac{12}{25}+\frac{5}{-8}+\frac{2}{-5}+\frac{13}{25}\)
\(=\left(\frac{3}{8}-\frac{5}{8}\right)+\left(\frac{12}{25}+\frac{13}{25}\right)-\frac{2}{5}\)
\(=-\frac{1}{4}+1-\frac{2}{3}\)
\(=\frac{1}{12}\)

\(-\dfrac{3}{16}+-\dfrac{3}{8}-\dfrac{5}{4}\)
\(=-\dfrac{3}{16}-\dfrac{3}{8}-\dfrac{5}{4}\)
\(=-\dfrac{3}{16}-\dfrac{6}{16}-\dfrac{20}{16}\)
\(=\dfrac{-3-6-20}{16}\)
\(=-\dfrac{29}{16}\)
\(\left(-\dfrac{25}{13}\right)+\dfrac{-9}{17}+\dfrac{12}{13}+\dfrac{25}{17}\)
\(=\left[\left(-\dfrac{25}{13}\right)+\dfrac{12}{13}\right]+\left[\left(-\dfrac{9}{17}+\dfrac{25}{17}\right)\right]\)
\(=-\dfrac{13}{13}+\dfrac{17}{17}\)
\(=-1+1\)
\(=0\)

a) Ta có: \(A=\dfrac{2}{7}+\dfrac{-3}{8}+\dfrac{11}{7}+\dfrac{1}{3}+\dfrac{1}{7}+\dfrac{5}{-8}\)
\(=\left(\dfrac{2}{7}+\dfrac{11}{7}+\dfrac{1}{7}\right)+\left(\dfrac{-3}{8}+\dfrac{-5}{8}\right)+\dfrac{1}{3}\)
\(=2-1+\dfrac{1}{3}\)
\(=1+\dfrac{1}{3}=\dfrac{4}{3}\)
b) Ta có: \(B=\dfrac{-3}{8}+\dfrac{12}{25}+\dfrac{5}{-8}+\dfrac{2}{-5}+\dfrac{13}{25}\)
\(=\left(\dfrac{-3}{8}+\dfrac{-5}{8}\right)+\left(\dfrac{12}{25}+\dfrac{13}{25}\right)+\dfrac{-2}{5}\)
\(=-1+1+\dfrac{-2}{5}\)
\(=-\dfrac{2}{5}\)
Giải:
A= 2/7+ -3/8 +11/7 +1/3 + 1/7 + 5/-8
A= (2/7+11/7+1/7)+(-3/8+-5/8)+1/3
A= 2+ (-1) + 1/3
A= 1+1/3
A= 4/3
B= -3/8 + 12/25 + 5/-8 + 2/-5 + 13/25
B= (-3/8+-5/8) + (12/25+13/25) + -2/5
B= -1 + 1 + -2/5
B=-2/5
Chúc bạn học tốt!
`-3/8 + 12/25 - 5/8 + 2/(-5) + 13/25`
`= -(3/8 + 5/8) + (12/25 + 13/25) - 2/5 `
`= -1 + 1 - 2/5`
`= -2/5`
\(\dfrac{-3}{8}+\dfrac{12}{25}-\dfrac{5}{8}+\dfrac{2}{-5}+\dfrac{13}{25}\)
\(=\left(\dfrac{-3}{8}-\dfrac{5}{8}\right)+\left(\dfrac{12}{25}+\dfrac{13}{25}\right)-\dfrac{2}{5}\)
\(=\dfrac{-8}{8}+\dfrac{25}{25}-\dfrac{2}{5}\)
\(=-1+1-\dfrac{2}{5}\)
\(=\dfrac{-2}{5}\)